How to study limit through computer-aided learning with conceptual-conflict strategy. (February 2019) - Mulyono, B; Kusumah, Y S; Rosjanuardi, R
Abstract: This article talks about how to help students studying limit through computer-aided learning (CAL) with conceptual-conflict strategy (CCS). In their learning activities students use computer for graphing and calculating, and they are conditioned in learning atmosphere which could trigger conflict of conceptual about what they already knew and what they just know. In this case, the topic discussed is about definition of limit intuitively. As we know that students already studied limit at senior high school, but some students still have misconception about limit. They had their own perception about limit, for instance, limit is a value of function at a point, the value of limit is a result of substituting a value x = c to a function f ( x ), and limit is a boundary value of a function that there is no any other value of the function higher than the value of limit. The result of implementation of CAL with CCS indicates that students realized that they had some misconceptions about limit, and then they became more understand how to determine a value of limit by considering the right- and left-hand limits.